Relationship between Emotional Intelligence with Verbal Aggressiveness in Street Children - Eka Yulianty Wulandary (International Consortium of Education and Culture Research Studies, 2020)
Verbal aggressiveness is a behavior that has a purpose to hurt other people’s feeling by saying harsh words, insulting, mocking, and threatening someone. Factor that underlie the emergence of verbal aggressiveness in street children, one of them is emotional intelligence. Emotional intelligence is ability to control oneself, have endurance when faced with a problem,self motivated, able to set the meed, ability to empathize and build relationships with others. The research mainly happen to understand relation between emotional intelligence and verbal aggressiveness in street children. This research method using quantitative approach. Subjects are picked by Incidental sampling techniques and involving 40 street children. Emotional intelligence scale is picked as collecting tool and also verbal aggressiveness scale. Data analysis uses Shpearman’s Rho technique. The result on Shpearman’s Rho correlation technique shows correlation (r) = -0,721 at a significant level (p) = 0,000 (p<0,05). The conclusion is there is a negative and significant correlation of the relationship between emotional intelligence with verbal aggressiveness in street children. So, if someone has low emotional intelligence, then verbal aggressiveness will be high.